Comparison of Perpendicular to the Coronal Plane versus Medial Inclination for C2 Pedicle Screw Insertion Assisted by 3D Printed Navigation Template. Issue 2 (11th October 2022) - Wu, Chao; Deng, Jiayan; Wang, Qing; Shen, Danwei; Qin, Binwei; Li, Tao; Wang, Xiangyu; Zeng, Baifang
Abstract : Objective: C2 pedicle screw insertion is very important in posterior upper cervical surgery. The traditional screw placement technique requires us to consider both medial inclination and cephalad angle, it is difficult to operate intraoperatively. This paper is to explore a novel method of C2 pedicle screw placement compared with traditional C2 pedicle screw. Methods: A total of 44 patients diagnosed with atlantoaxial fracture or instability from May 2018 to November 2020 were involved in this retrospective study, and they were divided into C2‐PPS group (perpendicular to the coronal plane C2 screw, 24 patients) and C2‐TPS group (traditional C2 pedicle screw, 20 patients). The diameter of the maximum tangential circle, distance between geometric center and median sagittal plane and screw length of PPS and TPS were measured based on the 3D model of C2, respectively. Then the 3D printed navigation templated were designed and manufactured by 3D printing to assisted the PPS and TPS placement, respectively. The surgical time and radiation exposure times during operation were recorded; the post‐operative grading criteria, deviation of screw entry point and deviation of screw angle of two groups were evaluated, respectively. Results: A total of 48 screws were inserted in the C2‐PPS group, and 40 screws were inserted in the C2‐TPS group. There were 46 screws with grade 0 (95.8%) in the PPS group and 31 screws with grade 0 (77.5%) in the TPS group, ( P  = 0.03). The radiation exposure times in the C2‐PPS group and C2‐TPS group were 4.7 ± 1.5 and 7.8 ± 3.8, respectively, ( P  = 0.045). The deviations of screw entry point in the C2‐PPS group and C2‐TPS group were 1.2 ± 0.8 mm and 3.2 ± 1.3 mm, respectively; the deviations of screw angle in the C2‐PPS group and C2‐TPS group were 2.1 ± 1.6° and 4.8 ± 2.0°, respectively, ( P  = 0.000). The diameters of the maximum tangential circle in the C2‐PPS group and C2‐TPS group were 5.5 ± 1.0 mm and 5.3 ± 0.9 mm, respectively. The distances between the geometric center and median sagittal plane in the C2‐PPS group and C2‐TPS group were 15.4 ± 2.3 mm and 18.0 ± 3.3 mm, respectively; The screw lengths in the C2‐PPS group and C2‐TPS group were 25.9 ± 3.2 mm and 27.6 ± 3.7 mm, respectively, ( P  = 0.000). Conclusion: Eighty percent of C2‐PPS corridor can accommodate a 3.5 mm diameter screw, and with an average screw length of 26 mm. Navigation templates assisted the C2‐PPS placement is less surgical time, less radiation exposure times, more safe and more accurate than C2‐TPS. Abstract : The C2 pedicle screw corridor perpendicular to the coronal plane could be quickly obtained by a perspective model with a three‐dimensional structure. Approximately 80% of the C2‐PPS corridor had a maximum diameter larger than 4 mm, which could safely accommodate a 3.5 mm diameter screw, with an average screw length of 26 mm. The technique of screw placement perpendicular to the coronal plane assisted by navigation templates is safer and more accurate than screw placement with medial inclination.